WORK-LIFE BALANCE PERCEPTIONS OF WOMEN IN THE IT AND ITES SECTORS IN KERALA: A RESEARCH STUDY (Journal of Pharmaceutical Negative Results, 2023)
The business landscape has undergone significant change as a result of the globalisation and information technology industries' steady growth. In addition to changing the employer-employee relationship, it has transformed the way that business is approached and the expectations and attitudes of employees while they are at work. Due to the diverse workforce and demanding climate of today, the responsibility of running a successful and profitable business falls primarily on the management. In today's competitive and demanding workplace, maintaining a healthy work-life balance is almost a necessity. In order to achieve work-life balance, employees' personal and professional lives must be in a state of equilibrium. 140 female workers in the IT and ITES sectors were used as the sample to examine how women employees perceive work-life balance and how that affects job satisfaction. In the investigation, a quantitative approach was used. 200 respondents completed a structured questionnaire that was given out in order to collect data. This data was then analysed using the proper statistical software. The data is found to be quantitative in the quantitative technique and can be divided into three categories: inferential, experimental, and simulation. An inferentially constructed database could be used to infer the characteristics or relationships of the targeted population. Because some of the variables are changed to see how they affect the other variables, the experimental form has a feature that offers a lot of flexibility in the study environment. One of the most important aspects of the simulation aspect is creating a synthetic environment where useful data and information can be produced. The results of the study show that an effective work-life balance will increase employee job satisfaction, which will improve organisational performance and give IT enterprises a competitive advantage.